2003
DOI: 10.1136/adc.88.1.27
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of sudden infant death syndrome

Abstract: Background: Twins compared to singletons are at increased risk of sudden infant death syndrome (SIDS). Aims: To compare the epidemiology of SIDS in twins and singletons and to test the hypothesis that monozygous (MZ) were at greater risk of SIDS than dizygous (DZ) twins. Methods: Data from the Office for National Statistics on all registered live births and infant deaths with registered cause of death "sudden unexpected death in infancy" in England and Wales from 1993 to 1998 were obtained, together with the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 10 publications
2
10
0
2
Order By: Relevance
“…The hypothesis that some SIDS deaths in twins may have been attributable to unrecognized prenatally acquired cerebral impairment associated with monozygotic monochorionic twinning was tested using, as a partial proxy for zygosity, a comparison of same-and opposite-sex twin SIDS mortality. No significant difference was found and it was concluded that zygosity was not an important factor (Platt & Pharoah, 2003).The study now reported complements the earlier one by extending the analysis to cover the years 1993 to 2003. The aim of this study is to examine time trends in SIDS mortality in twins and singletons and to determine whether the previous observations in birthweight-specific mortality and same-and opposite-sex twin differences are confirmed.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…The hypothesis that some SIDS deaths in twins may have been attributable to unrecognized prenatally acquired cerebral impairment associated with monozygotic monochorionic twinning was tested using, as a partial proxy for zygosity, a comparison of same-and opposite-sex twin SIDS mortality. No significant difference was found and it was concluded that zygosity was not an important factor (Platt & Pharoah, 2003).The study now reported complements the earlier one by extending the analysis to cover the years 1993 to 2003. The aim of this study is to examine time trends in SIDS mortality in twins and singletons and to determine whether the previous observations in birthweight-specific mortality and same-and opposite-sex twin differences are confirmed.…”
supporting
confidence: 67%
“…The hypothesis that some SIDS deaths in twins may have been attributable to unrecognized prenatally acquired cerebral impairment associated with monozygotic monochorionic twinning was tested using, as a partial proxy for zygosity, a comparison of same-and opposite-sex twin SIDS mortality. No significant difference was found and it was concluded that zygosity was not an important factor (Platt & Pharoah, 2003).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Even though the opposite-sex versus the same-sex twins stratification is only a proxy for chorionicity, it has been used in twin research. 29,30 Further, if we assume that assisted reproductive therapy confounds the association between maternal age and birth outcomes because of the differences in chorionicity, we would expect similar or worse outcomes among older versus younger mothers when only dichorionic twins were analyzed. Thus, the confounding effect of ATR, if any, is likely to manifest through mechanism(s) other than chorionicity.…”
Section: Discussionmentioning
confidence: 99%
“…4-6 9 Both preterm delivery and poor intrauterine growth are associated with the same social and economic factors that affect the risk of sudden infant death. 12 The most recent national data on SIDS show a striking increase in SIDS mortality with decreasing birth weight and this is likely to be related to the increasing levels of deprivation seen in SIDS families 13 Poor postnatal weight gain is also associated with an increased risk of SIDS. This seems to be independent of birth weight, prematurity, and social status and may be a useful additional tool in identifying infants at risk.…”
Section: Low Birth Weightmentioning
confidence: 99%